Implications of solid and liquid waste co-disposal on biodegradation and biochemical compatibility - Cook, Emily M., author; Bareither, Christopher A., advisor; Sharvelle, Sybil E., advisor; Ippolito, James A., committee member (Colorado State University. Libraries, 2018)
Co-disposal of solid and liquid waste in municipal solid waste (MSW) landfills can benefit landfill operations via enhancing waste moisture content and accelerating in situ waste biodegradation. However, implications of co-disposal on organic waste biodegradation are currently unknown and co-disposal in full-scale landfills is ad hoc. The objective of this study was to evaluate waste biodegradation and biochemical compatibility for different co-disposed solid and liquid wastes in MSW. To meet this objective, laboratory-scale reactors were operated to evaluate the potential impacts of co-disposal and ultimately to provide guidance for full-scale MSW landfill operations. Waste collected for this project was identified as MSW, special solid waste (SW), liquid waste (LW), and sludge waste (Sludge), such that reactor experiments were conducted with representative co-disposal combinations of MSW-SW, MSW-LW, and MSW-Sludge. The MSW-SW and MSW-Sludge reactors included landfill leachate as a liquid source to generate effluent; MSW-LW reactors were operated with unique liquid wastes. The MSW-LW reactors remained in the acid formation phase of biodegradation for the duration of the experiment. The liquid waste addition in the MSW-LW reactors was not an effective means to initiate biodegradation and is not recommended as an additive to fresh MSW without an inoculum that contains methanogenic microorganisms. All MSW-Sludge waste reactors and all but one set of the MSW-SW reactors reached methanogenesis. The solid and sludge wastes did not exhibit signs of biochemical incompatibility. The use of biochemical methane potential (BMP) assays as a selection tool for waste co-disposal was also evaluated. The BMP assays did not show good agreement with data from reactors that generated methane; therefore, use of BMP assays alone as a selection tool is not recommended.